Effects of Bio-Slurry and Chemical Fertilizer Application on Soil Properties and Food Safety of Tomato (Solanum lycopersicum Mill.) - Tseganesh Lolamo; Abate Feyissa Senbeta; Yadessa Gonfa Keneni; Getachew Sime (Applied and Environmental Soil Science)
This study evaluated the effects of bio-slurry (BS) and chemical fertilizer (CF) application on soil properties and food safety of tomato (Solanum lycopersicum Mill.). A field experiment consisting of 100% BS (5 ton BS ha−1), 100% CF (90 kg N·ha−1 + 30 kg P·ha−1 + 13 kg S·ha−1), and control was conducted. Soil samples from all the treatments were collected for their physico-chemical characteristics. The level of ten heavy metals in experimental soil and tomato fruit samples was also determined. Compared to CF and control, the application of BS improved soil physico-chemical characteristics. The BC significantly reduced the mean concentrations of Cd and Mn in the tomato fruit samples. The mean concentration of Ni (18.24 ± 0.61, 23.9 ± 0.3, and 9.66 ± 1.2 mg kg−1) and Mn (15.4 ± 2.4, 38 ± 3.3 and 21.8 ± 0.99 mg kg−1) in tomato fruit samples of BS-treated, CF-treated, and control soil, respectively, was above the safety limit set by the Food and Agriculture Organization/World Health Organization for human consumption. Similarly, the mean concentration of Cd (7.98 ± 0.72 and 3.29 ± 0.37 mg kg−1) in tomato fruit samples of CF-treated and control soil was above the safety limit. From this perspective, the consumption of these tomato fruits could be unsafe for human health with respect to Ni, Mn, and Cd toxicities. The application of BS could remediate the Cd toxicities, yet other scenarios of phytoremediation would be praiseworthy to address Ni, Cd, and Ni toxicities.